Dominasi Guru Perempuan dalam Pendidikan Anak Usia Dini: Persepsi Stakeholder - Mukhlis, Akhmad (Al-Athfal: Jurnal Pendidikan Anak, 2019)
This study aims to look at stakeholder perceptions women’s dominance and the lack of male participation as early childhood education teachers (PAUD). Research stakeholders consisted of the main stakeholders, teachers, and administrators of PAUD institutions and students' parents as supporting stakeholders. Although the most of research subjects did not reject male participation in PAUD, the findings of the study indicated that the most stakeholders considered women to have better competence than men in PAUD. Stakeholders also have a perception that men can participate in the development of physical-motor activities, arts, gender roles for male students and also filling leadership roles in PAUD institutions. To overcome the low participation of men in PAUD, it is hoped that government and university policies will be supported in developing male PAUD teacher candidates.